Association between Parkinson's disease and the risk of adverse cardiovascular events: a systematic review and meta-analysis - Hu, Yan; Xu, Shanxia (Frontiers in Cardiovascular Medicine, 2023)
Background: This review aims to examine the association of Parkinson's disease (PD) with the increased risk of cardiovascular events. Methods: PubMed, Embase, CENTRAL, and Scopus databases were electronically searched for papers published up to 5 th May 2023. Studies reporting the association between PD and subsequent risk of stroke, myocardial infarction (MI), and cardiovascular mortality were included.Results: Sixteen studies were included. Clinical data of 101712 PD patients were compared to the control group of 204901 patients without PD in the included studies. Meta-analysis showed that PD patients had an increased risk of stroke as compared to patients without PD (OR: 1.49 95% CI: 1.30, 1.72 I 2 =76%). Pooled analysis demonstrated no significant increase in the risk of MI (OR: 1.16 95% CI: 0.85, 1.59 I 2 =82%) and cardiovascular mortality (OR: 1.20 95% CI: 0.93, 1.54 I 2 =65%) in PD patients. However, data from cohort studies indicated a possibility of higher risk of MI (OR: 1.36 95% CI: 1.01, 1.84 I 2 =80%) and cardiovascular mortality (OR: 1.22 95% CI: 1.00, 1.60 I 2 =62%) in patients with PD.Patients with PD may have an increased risk of stroke as compared to age-and gender-matched general population. While our results show that PD does not increase the overall risk of MI and cardiovascular mortality, analysis of cohort studies alone demonstrated that these risks may be higher in patients with PD. The current evidence is of very low quality. Further prospective cohort studies from different countries that would account for important cardiovascular risk factors are needed to improve current evidence.